Patient Controlled Analgesia and an Alternative Protocol: A Comparison of Outcomes After Thoracic and Lumbar Surgery - Donelson, Will; Dean, Joey; Ablah, Elizabeth; Whitaker, Clara; Berg, Gina; McCormick, Kyle; Okut, Hayrettin; Whitaker, Camden (Kansas Journal of Medicine, 2022)
Introduction. Patient controlled analgesia (PCA) is a common form of pain management after spine surgeries, in which patients get custom control of their opioid dose. PCA has been demonstrated as a safe form of analgesia; however, use of PCA comes with risks that can be mitigated by opting for alternative pain management. This study aimed to compare the outcomes of patients using PCA to those with an alternative analgesia protocol that does not involve PCA. Methods. A retrospective chart review from January 2017 to July 2018 was conducted. Patients included in this study were those 18 or older who were admitted to a large midwestern tertiary medical center in Wichita, Kansas, and underwent thoracic or lumbar spinal surgery from a single spine surgeon. Data from patient demographics, comorbidities, and type of procedure were collected and compared to control for possible confounding variables. Patients were divided into two groups: patients receiving a PCA pain protocol postoperatively and those receiving a non-PCA protocol. Statistical analyses were performed and all tests with p < 0.05 were considered significant. Results. This study found patients in the PCA protocol had similar outcomes to those in the alternative analgesia protocol. This was true for both primary and secondary outcomes. The primary outcome was patient length of stay after the operation. Secondary outcomes included readmission rates, frequency of naloxone rescue, transfers to higher levels of care, and total opioid consumption. Conclusions. This study supports that a non-PCA protocol for postoperative pain management yields similar outcomes to a PCA protocol in the setting of thoracic and lumbar surgery.